(untitled) (Research, Society and Development, 2022)
Water is essential in the food and meat processing industry. The processing industry is one of the major consumers of water, and consequently, generators of a significant amount wastewater effluents which pollute the water bodies heavily. The objective of this study was to evaluate the cytotoxic potential of raw effluent, anaerobic and aerobic ponds, and surface water of the Cleopatra stream pre- and post-discharge of the effluent from a sausage industry by Allium cepa L. test. At different sampling timepoints, tests on the roots were conducted, as follows: control samples of the self-bulb (0 h), treatment with effluent or water (24 h), and recovery in filtered water (24 h). The results showed that the raw effluent is cytotoxic, because it inhibited the cell division completely. However, this inhibition was not permanent as, after the recovery time, the cells divided again at a rate greater than that of the control. Wastewater from the anaerobic and aerobic ponds and before and after discharge into the stream was not found to be cytotoxic. At the time of recovery, an increase in cell division was observed in samples treated with wastewater from the anaerobic and aerobic ponds, which is possibly caused due to the presence of organic matter. Despite the efficiency of treatment methods, it is necessary to conduct studies that monitor the effluents from the industry and stream waters to ascertain possible impacts on the environment.